The Importance of Supply Chain Management on Financial Optimization - Arawati Agus (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Many manufacturing companies are facing uncertainties and stiff competition both locally and globally, intensified by increasing needs for sophisticated and high value products from demanding customers. These companies are forced to improve the quality of their supply chain management decisions, products and reduce their manufacturing costs. With today’s volatile and very challenging global market, many manufacturing companies have started to realize the importance of the proper managing of their supply chains. Supply chain management (SCM) involves practices such as strategic supplier partnership, customer focus, lean production, postpone concept and technology & innovation. This study investigates the importance of SCM on financial optimization. The study measures production or SCM managers’ perceptions regarding SCM and level of performances in their companies. The paper also specifically investigates whether supply chain performance acts as a mediating variable in the relationship between SCM and financial optimization. These associations were analyzed through statistical methods such as Pearson’s correlation and a regression-based mediated analysis. The findings suggest that SCM has significant correlations with supply chain performance and financial optimization. In addition, the result of the regression-based mediated analysis demonstrates that supply chain performance mediates the linkage between SCM and financial optimization. The findings of the study provide a striking demonstration of the importance of SCM in enhancing the performances of Malaysian manufacturing companies. The result indicates that manufac-turing companies should emphasize greater management support for SCM implementation and a greater degree of attention for production integration and information flow integration in the manufacturing system in order to maximize profit and tzerimize cost.